Determinan Penggunaan Sistem Informasi Akuntansi Berbasis E-commerce - Desyana Putri (Mahesa Research Center, 2023)
This research aims to analyze the factors influencing the use of e-commerce-based accounting information systems. The study was conducted in one of the universities in Riau and North Sumatra Provinces. The sampling method employed convenience sampling, resulting in a sample size of 96 respondents. The research involved a combination of library and field research methods, including observation, interviews, correspondence, and questionnaires. Multiple linear regression analysis was used to determine the influence between dependent and independent variables. The research findings indicate that subjective norms and perceived ease of use affect the behavioral interest in using e-commerce-based accounting information systems, while attitudes have a relatively weaker influence on the behavioral interest in using e-commerce-based accounting information systems.